3=-4+t

Simple and best practice solution for 3=-4+t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3=-4+t equation:



3=-4+t
We move all terms to the left:
3-(-4+t)=0
We add all the numbers together, and all the variables
-(t-4)+3=0
We get rid of parentheses
-t+4+3=0
We add all the numbers together, and all the variables
-1t+7=0
We move all terms containing t to the left, all other terms to the right
-t=-7
t=-7/-1
t=+7

See similar equations:

| u+18/u=-9 | | (x+4)^3=7 | | 4+1-3x+8=-5x-7-3x | | -5a+5+6a=14-27 | | ​1.5​​k​​=3 | | 8 = r4+ 5 | | 1/3x+1/5=−2(3/4x−4) | | 9v-2v=35 | | 2a^2-3a=(5a^2-a+7) | | 14–3c=5 | | 2x+4=3(x–2)+1 | | 1/3x+1/5=−2(3/4x-4) | | 75=-7x+12 | | 3(x+1/2)=8 | | 50/p+5=-35+8p | | 5x-x-3=3x-3 | | -6=s-9 | | 7-6a=9-16 | | 2/3(n+6)=10 | | 1/13+h=0 | | x²+9x+9=0 | | 14s+35=-6s | | 5x+4+2x=19 | | 1/2x+1/3=3x-3 | | -14+2+7x+2x=8x-8-7 | | 1-198/n(n*n-1)=0.8 | | -(5/8)c=20 | | r+7=-7 | | 2(2x+1)=-2(5x-3)-5x | | 18x-(8x-7=67 | | 5x(27)=32 | | 4x-52=-5x+2 |

Equations solver categories